6q deletion in Waldenström macroglobulinaemia negatively affects time to transformation and survival. (11th August 2020) - García‐Sanz, Ramón; Dogliotti, Irene; Zaccaria, Gian Maria; Ocio, Enrique María; Rubio, Araceli; Murillo, Ilda; Escalante, Fernando; Aguilera, Carmen; García‐Mateo, Aránzazu; García de Coca, Alfonso; Hernández, Roberto; Dávila, Julio; et al.
Summary: Deletion of the long arm of chromosome 6 (del6q) is the most frequent cytogenetic abnormality in Waldenström macroglobulinaemia (WM), occurring in approximately 50% of patients. Its effect on patient outcome has not been completely established. We used fluorescence in situ hybridisation to analyse the prevalence of del6q in selected CD19+ bone marrow cells of 225 patients with newly diagnosed immunoglobulin M (IgM) monoclonal gammopathies. Del6q was identified in one of 27 (4%) cases of IgM‐monoclonal gammopathy of undetermined significance, nine of 105 (9%) of asymptomatic WM (aWM), and 28/93 (30%) of symptomatic WM (sWM), and was associated with adverse prognostic features and higher International Prognostic Scoring System for WM (IPSSWM) score. Asymptomatic patients with del6q ultimately required therapy more often and had a shorter time to transformation (TT) to symptomatic disease (median TT, 30 months vs. 199 months, respectively, P  < 0·001). When treatment was required, 6q‐deleted patients had shorter progression‐free survival (median 20 vs. 47 months, P  < 0·001). The presence of del6q translated into shorter overall survival (OS), irrespective of the initial diagnosis, with a median OS of 90 compared with 131 months in non‐del6q patients ( P  = 0·01). In summary, our study shows that del6q in IgM gammopathy is associated with symptomatic disease, need for treatment and poorer clinical outcomes.